2006
DOI: 10.1002/hep.21285
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of acidic sphingomyelinase in murine hepatic ischemia-reperfusion injury

Abstract: The molecular mechanisms of hepatic ischemia/reperfusion (I/R) damage are incompletely understood. We investigated the role of ceramide in a murine model of warm hepatic I/R injury. This sphingolipid induces cell death and participates in tumor necrosis factor (TNF) signaling. Hepatic ceramide levels transiently increased after the reperfusion phase of the ischemic liver in mice, because of an early activation of acidic sphingomyelinase (ASMase) followed by acid ceramidase stimulation. In vivo administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 51 publications
10
91
2
Order By: Relevance
“…After a midline laparotomy, hepatic inflow to the median and left lobes was occluded by application of a micro-vascular clamp (Biemer clip, 0.29-0.39 N) for 60-90 min as described previously [12,13] to prevent hepatic blood flow for 90 minutes. Mesenteric venous congestion was prevented by portal decompression through the right and caudate lobes.…”
Section: Partial Hepatic Ischemiamentioning
confidence: 99%
See 2 more Smart Citations
“…After a midline laparotomy, hepatic inflow to the median and left lobes was occluded by application of a micro-vascular clamp (Biemer clip, 0.29-0.39 N) for 60-90 min as described previously [12,13] to prevent hepatic blood flow for 90 minutes. Mesenteric venous congestion was prevented by portal decompression through the right and caudate lobes.…”
Section: Partial Hepatic Ischemiamentioning
confidence: 99%
“…Mesenteric venous congestion was prevented by portal decompression through the right and caudate lobes. Blood samples and liver biopsies were taken at different periods after reperfusion for further evaluation, typically 4-6 hours postreperfusion when massive liver injur is observed [12,13]. Control animals were sham operated.…”
Section: Partial Hepatic Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocytes were chosen as target cells in this assay because they are classic target cells for GVHD and use the sphingomyelin pathway for apoptosis. 20,21,43 Coincubation with 0 to 2 ϫ 10 6 alloactive splenic T cells increased hepatocyte apoptosis from 4.7% (Ϯ 0.7%) to 33.8% (Ϯ 1.9%) by 16 hours, detected by nuclear morphologic changes ( Figure 4A). In contrast, syngeneic LP hepatocytes did not undergo significant apoptosis above baseline (not shown).…”
Section: Ctl-induced Hepatocyte Apoptosis Requires Ceramide-rich Platmentioning
confidence: 99%
“…16,17 Recent studies have indicated that the sphingomyelin pathway and its second messenger ceramide regulate TNF superfamily receptor-induced apoptosis in some systems, 18,19 as well as apoptosis in select liver and gastrointestinal (GI) stress responses in vivo. Ceramide generation occurs rapidly in hepatic ischemiareperfusion injury, 20 TNF-induced hepatitis/cirrhosis, 21 and radiation-induced GI toxicity. 22 Genetic or pharmacologic inhibition of acid sphingomyelinase (ASMase)-mediated ceramide generation markedly attenuates pathogenesis of these syndromes.…”
Section: Introductionmentioning
confidence: 99%